Differences in professional liability in health care – legal regulations - Huzarska, Dorota; Piątkiewicz, Jacek Antoni; Nowacki, Piotr; Huzarska, Joanna; Szpak, Andrzej (Polish Journal of Public Health, 2010)
Health care professionals, in particular physicians, nurses, pharmacists, laboratory diagnosticians play a special role in society with regard to the circumstances that they are responsible for the most important humane values as human life and health. The practising of these professions demands from high qualifications and high social responsibility health care professionals. Surveillance over the proper practicing of health care professions fulfil appropriate self-governmental organisations of medical professions, in particular through conducting of procedures in the subject of professional liability. The content of this article consists of the analysis and comparison of legal regulations concerning professional liability in health care professions in connexion with the law on Medical Chambers coming into force on 1 January 2010. Legal regulations in the subject of the professional liability in health care occur in different legal acts; they are not always consistent in defining the principles of liability in particular health care professions. The differences concern in particular the scope of professional liability, the kinds of punishment in case of professional malpractice and the procedures. Breaking of the legal regulations and ethical principles concerning practicing of health care professions by representatives of different professions does not lead to the same consequences. Legal regulations concerning professional liability in health care cause numerous reservations and therefore it is advisable to unify the regulations.